2010
DOI: 10.1128/jcm.00799-10
|View full text |Cite
|
Sign up to set email alerts
|

Cholera Toxin Production by the El Tor Variant ofVibrio choleraeO1 Compared to Prototype El Tor and Classical Biotypes

Abstract: Vibrio cholerae O1 El Tor variant strains produced much more cholera toxin than did prototype El Tor strains. The amount of cholera toxin produced by El Tor variant strains both in vitro and in vivo was more or less equivalent to that produced by classical strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 17 publications
2
54
0
4
Order By: Relevance
“…Another common ET isolate, N16961, produced more CT than other ET strains, which was expected, as this strain has previously been found to produce more CT than other ET strains and, as observed in this study for 2010EL-1786 (Fig. 1B), at levels that overlapped the amount expressed by AET strains (31). These results confirm results by others that 2010EL-1786 expresses ϳ2-fold more CT than N16961 and ϳ10-fold more than C6706 (a strain closely related to C6709) (17) and that AET strains in general produce more CT and induce secretion of more fluid in rabbit ileal loops (31).…”
Section: Overproduction Of Secreted Toxins By An Aet Isolate From Haitisupporting
confidence: 65%
“…Another common ET isolate, N16961, produced more CT than other ET strains, which was expected, as this strain has previously been found to produce more CT than other ET strains and, as observed in this study for 2010EL-1786 (Fig. 1B), at levels that overlapped the amount expressed by AET strains (31). These results confirm results by others that 2010EL-1786 expresses ϳ2-fold more CT than N16961 and ϳ10-fold more than C6706 (a strain closely related to C6709) (17) and that AET strains in general produce more CT and induce secretion of more fluid in rabbit ileal loops (31).…”
Section: Overproduction Of Secreted Toxins By An Aet Isolate From Haitisupporting
confidence: 65%
“…With the differences in the locations of where these diverse variants are being isolated come the inherent differences in genotypic and phenotypic profiles, as previously described elsewhere (28,29,33,39,44,45). An alarming concern has been the growing number of unpublished reports and one recently published report (16) revealing various amounts of cholera toxin being produced by the different El Tor variants isolated. Our initial clinical patient profiles (Table 1) revealed that the patients all suffered from severe watery diarrhea, a hallmark manifestation of cholera.…”
Section: Vol 49 2011 Characterization Of Clinical El Tor Variant Ismentioning
confidence: 99%
“…These El Tor variants have become a major focus of research, since other El Tor variants also have been identified in Asia and Mozambique (29,34,35,38) and recently have been a focus of attention in Haiti (1,6,7,8,9). Of particular concern are the recently published results indicating that some of the clinically isolated El Tor variants produce different levels of cholera toxin, including some isolates that produce higher levels than classical biotype strains (16). Although evidence has been presented demonstrating that the El Tor biotype has globally displaced the classical biotype (19,42), the emergence of El Tor variants has warranted the use of standard genotypic and phenotypic assays to determine the biotype background of new isolates.…”
mentioning
confidence: 99%
“…The amount of CT produced was measured as described previously (32,33) during the growth of the representative strains from Zanzibar in AKI medium and compared with prototype El Tor and classical strains. It was found that all the El Tor variant strains from Zanzibar produced significantly larger amounts of CT in vitro than most strains of prototype El Tor (P Ͻ 0.001, MannWhitney U test) (Fig.…”
mentioning
confidence: 99%